Case Report: Humanized Selective CD19CAR-T Treatment Induces MRD-Negative Remission in a Pediatric B-ALL Patient With Primary Resistance to Murine-Based CD19CAR-T Therapy - Wang, Kai; Zhao, Yu; Wang, Xuan; Wang, Bin; Qin, Maoquan; Zhu, Guanghua; Wu, Huantong; Liu, Zhongfeng; Zheng, Xueling; Zheng, Huyong; Chen, Zhiguo (Frontiers in Immunology, 2020)
Background: CD19 chimeric antigen receptor T cell (CD19CAR-T) has shown great potential to treat acute B cell lymphoblastic leukemia (B-ALL) and B cell lymphoma, and most of anti-CD19 scFv are derived from murine antibody sequences. However, about 10%-20% of B-ALL patients exhibit primary resistance to murine-based CD19CAR-T (CD19mCAR-T). Herein, we report that a humanized selective CD19CAR-T (CD19hsCAR-T) may offer a solution to this problem. Case description: A 10-year old boy was diagnosed with high-risk B-ALL in Mar., 2013, and relapsed in Oct., 2018, after he underwent haplo-identical hematopoietic stem cell transplantation (HSCT) in 2017. The patient then received haplo-identical CD19mCAR-T infusions twice following induction chemotherapy with Vincristine, Dexamethasone and Asparaginase (VDL), but no response was observed. We further treated this patient with CD19hsCAR-T following chemotherapy with Vindesine, Idarubicin, Dexamethasone, and Pegylated Asparaginase (VDLD) plus bortezomib. The patient achieved minimal residual disease-negative (MRDneg) complete remission with incomplete hematopoietic recovery (CRi), and remained in CRi for more than 8 months with manageable side effect. The patient, unfortunately, died of unidentified pulmonary infection on Jan. 25 2020. Conclusion: CD19hsCAR-T may have the potential to induce remission in patients who are primarily refractory to CD19mCAR-T.